Pulmonary thromboembolism: retrospective study of necropsies performed over 24 years in a university hospital in Brazil - Golin, Valdir; Sprovieri, Sandra Regina Schwarzwälder; Bedrikow, Rubens; Salles, Mauro José Costa (São Paulo Medical Journal, 2002)
CONTEXT: Pulmonary thromboembolism is the third most frequent cause of morbidity and mortality among acute cardiovascular diseases. The incidence of pulmonary embolism in necropsies has remained unchanged over the last few decades. Cardiac diseases, neoplasia, trauma, recent surgery and systemic diseases are important predisposing clinical conditions. The relationship between male and female sexes is estimated at 1.24. Various studies have shown an increase in morbidity in spring and autumn. There is great difficulty in precise anatomopathological diagnosis in relation to the localization of the emboli in the pulmonary vessels, although they are preferentially located in the right lung and lower lobes. OBJECTIVE: To study the incidence of lethal and non-lethal pulmonary thromboembolism in relation to epidemiological and anatomical variables. DESIGN: Retrospective study performed via reports on the necropsy findings. SETTING: University hospital providing tertiary-level attendance. SAMPLE: 16,466 consecutive necropsies performed from January 1972 to December 1995. MAIN MEASUREMENTS: Frequency of lethal and non-lethal pulmonary thromboembolism, predisposing diseases, occurrence in relation to the seasons of the year, and location where the embolus is lodged. RESULTS: Pulmonary thromboembolism was found in 4.7% of all the necropsies performed. There was a predominance of lethal cases (68.2%). There was no difference in relation to sex or seasons of the year for the occurrence of this disease. Cardiovascular diseases were more frequently associated with thromboembolic phenomena. With regard to the location where the embolus was lodged, various lung segments showed greater incidence of being bilaterally compromised. CONCLUSION: Over the period of this study, it was observed that there was a reduction in the incidence of pulmonary thromboembolism, which was probably due to the increase in prophylactic measures over the last few decades. Nonetheless, lethal thromboembolism predominated in frequency, probably because of the abrupt onset of a condition of attack across a large area of the lung, lack of clinical suspicions and consequently a lack of early diagnosis, and delay in instituting fibrinolytic therapy in the cases with hemodynamic repercussions or a large number of lung segments affected.